YOUR RIGHT ARM FOR A PUBLICATION IN AER?. (24th March 2013) - ATTEMA, ARTHUR E.; BROUWER, WERNER B.F.; VAN EXEL, JOB
<x xml:space="preserve">Abstract</x> The time tradeoff (TTO) method is popular in medical decision making for valuing health states. We use it to elicit economists' preferences for publishing in top economic journals and for living without limbs. The economists value journal publications highly and have a clear preference among them, with the American Economic Review (AER) the most preferred. Their responses imply they would sacrifice more than half a thumb for an AER publication. These TTO results are consistent with ranking and willingness to pay results, and indicate that journal preferences are not entirely determined by impact factors or by expectations of a salary increase following a publication in a prestigious journal. (JEL A10, B41, I10)